G protein‐dependent signaling triggers a β‐arrestin‐scaffolded p70S6K/ rpS6 module that controls 5'TOP mRNA translation. Issue 3 (3rd January 2018) - Trefier, Aurelie; Musnier, Astrid; Landomiel, Flavie; Bourquard, Thomas; Boulo, Thomas; Ayoub, Mohammed Akli; Leon, Kelly; Bruneau, Gilles; Chevalier, Manon; Durand, Guillaume; Blache, Marie‐Claire; Inoue, Asuka; et al.
Abstract : Many interaction partners of β‐arrestins intervene in the control of mRNA translation. However, how β‐arrestins regulate this cellular process has been poorly explored. In this study, we show that β‐arrestins consti‐tutively assemble a p70S6K/ribosomal protein S6 (rpS6) complex in HEK293 cells and in primary Sertoli cells of the testis. We demonstrate that this interaction is direct, and experimentally validate the interaction interface between β‐arrestin 1 and p70S6K predicted by our docking algorithm. Like most GPCRs, the biological function of follicle‐stimulating hormone receptor (FSHR) is transduced by G proteins and β‐arrestins. Upon follicle‐stimulating hormone (FSH) stimulation, activation of G protein‐dependent signaling enhances p70S6K activity within the β‐arrestin/p70S6K/rpS6 preassembled complex, which is not recruited to the FSHR. In agreement, FSH‐induced rpS6 phosphorylation within the β‐arrestin scaffold was decreased in cells depleted of Gαs . Integration of the cooperative action of β‐arrestin and G proteins led to the translation of 5' oligopyrimidine track mRNA with high efficacy within minutes of FSH input. Hence, this work highlights new relationships between G proteins and β‐arrestins when acting cooperatively on a common signaling pathway, contrasting with their previously shown parallel action on the ERK MAP kinase pathway. In addition, this study provides insights into how GPCR can exert trophic effects in the cell.—Tréfier, A., Musnier, A., Landomiel, F., Bourquard, T., Boulo, T., Ayoub, M. A., León, K., Bruneau, G., Chevalier, M., Durand, G., Blache, M.‐C., Inoue, A., Fontaine, J., Gauthier, C., Tesseraud, S., Reiter, E., Poupon, A., Crépieux, P. Gprotein‐dependent signaling triggers a β‐arrestin‐scaffolded p70S6K/ rpS6 module that controls 5'TOP mRNA translation. FASEB J. 32, 1154‐1169 (2018). www.fasebj.org